Endobronchial autologous bone marrow–mesenchymal stromal cells in idiopathic pulmonary fibrosis: a phase I trial. Issue 2 (28th June 2021) - Campo, Arantza; González-Ruiz, José María; Andreu, Enrique; Alcaide, Ana B.; Ocón, María M.; De-Torres, Juan; Pueyo, Jesús; Cordovilla, Rosa; Villaron, Eva; Sanchez-Guijo, Fermín; Barrueco, Miguel; Nuñez-Córdoba, Jorge; et al.
Rationale: Idiopathic pulmonary fibrosis (IPF) has a dismal prognosis. Mesenchymal stromal cells (MSCs) have shown benefit in other inflammatory diseases. Objectives: To evaluate the safety and feasibility of endobronchial administration of bone marrow autologous MSCs (BM-MSC) in patients with mild-to-moderate IPF. Methods: A phase I multicentre clinical trial (ClinicalTrials.gov NCT01919827) with a single endobronchial administration of autologous adult BM-MSCs in patients diagnosed with mild-to-moderate IPF. In a first escalating-dose phase, three patients were included sequentially in three dose cohorts (10×10 6, 50×10 6 and 100×10 6 cells). In a second phase, nine patients received the highest tolerated dose. Follow-up with pulmonary function testing, 6-min walk test and St George's Respiratory Questionnaire was done at 1, 2, 3, 6 and 12 months, and with computed tomography at 3, 6 and 12 months. Results: 21 bone marrow samples were obtained from 17 patients. Three patients were excluded from treatment due to chromosome aberrations detected in MSCs after culture, and one patient died before treatment. Finally, 13 patients received the BM-MSC infusion. No treatment-related severe adverse events were observed during follow-up. Compared to baseline, the mean forced vital capacity showed an initial decline of 8.1% at 3 months. The number of patients without functional progression was six (46%) at 3 months and three (23%) at 12 months. Conclusions: The endobronchial infusion of BM-MSCs did not cause immediate serious adverse events in IPF patients, but a relevant proportion of patients suffered clinical and/or functional progression. Genomic instability of BM-MSCs during culture found in three patients may be troublesome for the use of autologous MSCs in IPF patients. Endobronchial autologous mesenchymal stromal cells (MSCs) did not cause direct serious adverse events in IPF patients. However, significant progression was seen in seven out of 13 patients. Genomic instability of autologous MSCs may limit use in IPF. https://bit.ly/39akv7z